1998
DOI: 10.1002/(sici)1096-9136(199803)15:3<228::aid-dia551>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral sensory nerve dysfunction in children and adolescents with Type 1 diabetes mellitus

Abstract: The aim of the present study was to investigate peripheral sensory nerve function in diabetic children and adolescents without neurological symptoms. Ninety-two children and adolescents with Type 1 (insulin-dependent) diabetes mellitus (mean +/- SD age: 14.2 +/- 2.1 years, diabetes duration: 5.8 +/- 3.0 years) and 80 healthy control subjects (age: 13.8 +/- 2.2 years) matched for age, sex, body mass index, and height standard deviation score were involved in the study. Using a sine-wave transcutaneous stimulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 22 publications
1
18
0
1
Order By: Relevance
“…Abnormalities in peripheral nerve function were common in patients with type 1 and type 2 diabetes (27 and 21%, respectively) based on quantitative sensory tests. The rate in type 1 diabetes is consistent with data from other authors (48,49) but is considerably lower than the rate of 63% in Danish patients screened in 1995 (38). In the latter study, risk factors for neuropathy included age, male sex, and elevated AER.…”
Section: Diabetes Complications In Type 2 Diabetessupporting
confidence: 91%
“…Abnormalities in peripheral nerve function were common in patients with type 1 and type 2 diabetes (27 and 21%, respectively) based on quantitative sensory tests. The rate in type 1 diabetes is consistent with data from other authors (48,49) but is considerably lower than the rate of 63% in Danish patients screened in 1995 (38). In the latter study, risk factors for neuropathy included age, male sex, and elevated AER.…”
Section: Diabetes Complications In Type 2 Diabetessupporting
confidence: 91%
“…Several studies mentioning normative data (Barkai et al 1998;Kenton et al 2003) using the median and range of values, which indicates a large variability, could not be used because of incomplete data.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies confirmed the association between poor glycemic control and an increasing risk for nephropathy [100-102], retinopathy [95,103,104], and neuropathy [105-109]. A large proportion of patients, however, fails to achieve glycemic targets [110-112].…”
Section: Treatmentmentioning
confidence: 99%